2005
DOI: 10.1111/j.1742-4801.2005.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the management of necrotising fasciitis in neonates

Abstract: Necrotising fasciitis is a severe, life-threatening soft tissue infection. It produces an extensive cellulitis with severe involvement of subcutaneous tissue, fascia, muscle or both, resulting in necrosis of the tissue. All age groups, including neonates, can be affected. Patients with necrotising fasciitis present with more severe constitutional symptoms and have a poor outcome, unless aggressive antibiotic therapy and surgical debridement are instituted promptly. The debridement of necrotic tissue is imperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…There has been description of various modern form of wound dressing materials for acute and chronic wounds of skin, which include activated charcoal, alginates, hyaluronic acid, hydrofibers, hydrogels, hydrocolloids, impregnated gauze, collagen, moist methods, proteolytic enzymes, foams, semipermeable membranes and silver dressings [33]. There has been successful use of alginate dressing in a neonate [34]. However, they are not in common use in children.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been description of various modern form of wound dressing materials for acute and chronic wounds of skin, which include activated charcoal, alginates, hyaluronic acid, hydrofibers, hydrogels, hydrocolloids, impregnated gauze, collagen, moist methods, proteolytic enzymes, foams, semipermeable membranes and silver dressings [33]. There has been successful use of alginate dressing in a neonate [34]. However, they are not in common use in children.…”
Section: Treatmentmentioning
confidence: 99%
“…This study, however, was not done specifically in children suffering from NF. There is one report combining use of alginate dressing and VAC in a neonate with good results [34]. More studies are needed for widespread use of these new techniques in children and neonates.…”
Section: Treatmentmentioning
confidence: 99%
“…Most authors from the paediatric literature stress that early and aggressive surgical debridement is vital in halting the progression of soft tissue necrosis and the ongoing release of bacterial toxins [1][2][3][4]. However, a group of authors has recently suggested withholding surgery and intensive care in all children with acute NF, reporting that cutaneous gangrene will naturally separate from healthy skin within 8 days [5].…”
Section: Discussionmentioning
confidence: 94%
“…We read the article ‘An approach to the management of necrotizing fasciitis in neonates’ in the June 2005 issue of this journal (1). As the authors mentioned, necrotising fasciitis (NF) is a severe life‐threatening soft‐tissue infection.…”
mentioning
confidence: 99%